Preparation method of Cu3Sn alloy electrocatalyst and application of Cu3Sn alloy electrocatalyst in urea synthesis

By preparing Cu3Sn alloy electrocatalyst, the problem of slow kinetics in the synthesis of urea from nitrate and carbon dioxide was solved, and efficient and environmentally friendly urea synthesis was achieved. The catalyst yield and Faraday efficiency were significantly improved, making it suitable for the electrocatalytic co-reduction reaction of nitrate and carbon dioxide.

CN120625100APending Publication Date: 2025-09-12HENAN NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511076833.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-01
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

In the existing technology, the kinetics of synthesizing urea from nitrate and carbon dioxide are slow and there are many by-products, resulting in low urea yield and Faradaic efficiency, making it difficult to apply it in large-scale industrial applications. There is an urgent need to design high-performance catalysts.

Method used

A Cu3Sn alloy electrocatalyst was prepared by a simple sintering reduction method. By mixing glucose, dicyandiamide, copper chloride and stannous chloride dihydrate and sintering them in a hydrogen/argon mixed atmosphere, a catalyst capable of catalyzing the co-reduction of nitrate and carbon dioxide to urea was prepared.

Benefits of technology

The highly efficient catalytic co-reduction of nitrate and carbon dioxide to urea was achieved under mild conditions, with a catalyst yield of 539.8 μgh-1mg-1 and a Faradaic efficiency of 50.5%, avoiding the fossil fuel consumption and pollutant emissions in the traditional high-temperature and high-pressure process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120625100A_ABST
    Figure CN120625100A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Cu3Sn alloy electrocatalyst and application of the Cu3Sn alloy electrocatalyst in urea synthesis. The preparation method comprises the specific preparation steps that glucose, dicyandiamide, copper chloride and stannous chloride dehydrate are ground and mixed to be uniform, and a material A is obtained; transferring the obtained material A into a tubular furnace, sintering for 2 hours at 420-500 DEG C in a hydrogen / argon mixed atmosphere, and naturally cooling to room temperature to obtain a material B; and uniformly grinding the obtained material B to obtain the Cu3Sn alloy electrocatalyst. The Cu3Sn alloy electrocatalyst can be used in a reaction system for co-reduction of nitrate and carbon dioxide into urea through electrocatalysis. Compared with a traditional industrial method, the method for preparing urea by catalyzing co-reduction of nitrate and carbon dioxide through the prepared Cu3Sn alloy electrocatalyst consumes greenhouse gas and does not discharge pollutants into air.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper-tin alloy electrocatalysts and catalytic reduction of carbon dioxide and nitrate to synthesize urea, and particularly relates to a preparation method of a Cu3Sn alloy electrocatalyst and application thereof in urea synthesis. Background Art

[0002] Urea is not only an essential fertilizer for crops but also plays a vital role in textiles, plastics, pharmaceuticals, and energy carriers. In industrial production, urea is synthesized into ammonia via the Haber-Bosch reaction, which then reacts with carbon dioxide to form urea via the Bosch-Meiser coupling reaction. Both processes require continuous high-temperature and high-pressure reaction conditions, consuming significant amounts of fossil fuels and releasing carbon dioxide into the air, contradicting the principles of green production and sustainable development. Using electrocatalytic technology under mild conditions, small nitrogen-containing substances (such as nitrate, nitrite, nitric oxide, and nitrogen) can be co-converted with carbon dioxide into high-value-added products, achieving green and sustainable material production. This offers an attractive alternative to traditional industrial urea production. Nitrates, due to their low dissociation energy, are a high-quality nitrogen source for electrocatalytic urea synthesis and have attracted widespread attention. However, the synthesis of urea from nitrates and carbon dioxide requires the transfer of 16 electrons and 18 protons, resulting in slow kinetics and numerous byproducts. This results in low urea yields and faradaic ratios, making large-scale industrial application difficult. The design of high-performance catalysts is urgently needed. The key to electrochemical urea synthesis is CN coupling, which directly couples carbon dioxide through carbon-nitrogen intermediates or nitrogen intermediates. However, the direct coupling of nitrogen intermediates and carbon dioxide requires a high energy barrier, which exacerbates side reactions. The current copper catalysts can precisely match the LUMOπ orbital energy level of nitrate ions, promoting electron transfer from the catalyst to nitrate ions, significantly reducing the reaction energy barrier, and are more resistant to nitrogen intermediates (such as NO2 - The adsorption strength of tin (NO) is moderate and is widely used in NO3RR, while tin has abundant valence electron resources and can form strong interactions with carbon atoms in molecules, which is conducive to the adsorption and activation of carbon dioxide and is widely used in carbon dioxide reduction. The multifunctional synergistic advantages of alloy catalysts have been favored by researchers in the electrochemical synthesis of urea. Therefore, it is very necessary to explore the preparation of urea by catalyzing nitrate and carbon dioxide reduction of copper-tin alloys. The present invention synthesizes Cu3Sn alloy electrocatalysts by simple sintering reduction, which can be used in the reaction system of electrocatalytic nitrate and carbon dioxide co-reduction to urea. There is currently no relevant report on this catalyst. In addition, this method provides theoretical guidance for efficient CN coupling synthesis. Summary of the Invention

[0003] The technical problem solved by the present invention is to provide a preparation method of a Cu3Sn alloy electrocatalyst and its application in urea synthesis. The method prepares the Cu3Sn alloy electrocatalyst by a simple sintering reduction method. The prepared catalyst can be used in a reaction system for the electrocatalytic co-reduction of nitrate and carbon dioxide to urea.

[0004] The present invention adopts the following technical solution to solve the above technical problems, a method for preparing a Cu3Sn alloy electrocatalyst, and its specific preparation steps are:

[0005] Step S1, grinding and mixing glucose, dicyandiamide, copper chloride and stannous chloride dihydrate to obtain material A, wherein the mass ratio of glucose, dicyandiamide, copper chloride and stannous chloride dihydrate is 0.2:0.08:0.0305:012;

[0006] Step S2, transferring the material A obtained in step S1 into a tube furnace, sintering it at 420-500° C. for 2 h in a hydrogen / argon mixed atmosphere, and then naturally cooling it to room temperature to obtain material B;

[0007] Step S3, grinding the material B obtained in step S2 uniformly to obtain a Cu3Sn alloy electrocatalyst.

[0008] It is further defined that the glucose, dicyandiamide, copper chloride and stannous chloride dihydrate in step S1 are ground under a heating lamp for 10 to 20 minutes; and the grinding time in step S3 is 30 to 50 minutes.

[0009] It is further defined that the volume percentage of hydrogen in the hydrogen / argon mixed atmosphere in step S2 is 10%, and the flow rate of the hydrogen / argon mixed atmosphere is 50-100 mL / min.

[0010] The preparation method of the Cu3Sn alloy electrocatalyst of the present invention comprises the following specific preparation steps:

[0011] Step S1, grinding 0.2 g of glucose, 0.08 g of dicyandiamide, 0.0305 g of copper chloride and 0.12 g of stannous chloride dihydrate in a grinding mortar for 15 min to obtain material A;

[0012] Step S2: Material A obtained in step S1 was placed in a hydrogen / argon mixed atmosphere at a flow rate of 100 mL / min, and hydrogen and argon were first passed through for 30 minutes before heating, and then heated to 500°C at a heating rate of 5°C / min and kept at this temperature for 2 hours to obtain material B;

[0013] Step S3: Grind the material B obtained in step S2 in a mortar to obtain a Cu3Sn alloy electrocatalyst.

[0014] The Cu3Sn alloy electrocatalyst of the present invention is used in the synthesis of urea by reducing carbon dioxide and nitrate. The specific process is as follows: 2 mg of the electrocatalyst prepared above is dispersed in a mixed solution of water, ethanol and Nafion, and after ultrasonic dispersion, the solution is dripped onto carbon paper and dried under a heat lamp. H-type electrodes are used for testing, with an Ag / AgCl electrode and a platinum sheet serving as the reference electrode and the counter electrode, respectively. The electrolyte is a 0.1M KNO3+0.1M KHCO3 solution saturated with carbon dioxide. The yield of urea synthesis catalyzed by the Cu3Sn alloy electrocatalyst reaches 539.8 μg / h. -1 mg -1 , the Faraday efficiency reaches 50.5%.

[0015] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0016] 1. Compared with traditional industrial methods, the method for preparing urea by catalyzing the co-reduction of nitrate and carbon dioxide using the Cu3Sn alloy electrocatalyst prepared by the present invention consumes greenhouse gases and does not emit pollutants into the air.

[0017] 2. The Cu3Sn alloy electrocatalyst provided by the present invention is evaluated by the following method: the catalytic performance of the catalyst is tested using an H-type electrode and an electrochemical workstation. The catalyst is ultrasonically dispersed in a mixed solution of water, ethanol and Nafion. After uniform dispersion, an appropriate amount is added dropwise to carbon paper and allowed to dry naturally. The electrolyte is 0.1M KNO3+0.1M KHCO3 solution. Linear sweep voltammetry (LSV) and cyclic voltammetry (CV) tests are carried out in an electrolyte saturated with carbon dioxide, and urea is detected using diacetyl monoxime. The results show that the maximum urea yield synthesized by the Cu3Sn alloy electrocatalyst is 539.8μgh. -1 mg -1 , the Faraday efficiency reaches 50.5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a scanning electron microscope image of product C prepared in Example 1.

[0019] Figure 2 1 is the XRD pattern of the product C prepared in Example 1 and the electrocatalysts of Comparative Examples 1 to 7.

[0020] Figure 3 1 is the LSV diagram of the product C prepared in Example 1 and the electrocatalysts of Comparative Examples 1 to 7.

[0021] Figure 4 Graphs of urea yield and Faradaic efficiency at -0.5 V vs. RHE for product C prepared in Example 1 and comparative examples 1 to 7. DETAILED DESCRIPTION

[0022] The above contents of the present invention are further described in detail below through examples, but this should not be understood as limiting the scope of the above subject matter of the present invention to the following examples. All technologies implemented based on the above contents of the present invention fall within the scope of the present invention.

[0023] Example 1

[0024] Step S1: 0.2 g of glucose, 0.08 g of dicyandiamide, 0.0305 g of copper chloride and 0.12 g of stannous chloride dihydrate were weighed and ground in a grinding mortar for 15 min to obtain material A;

[0025] Step S2: Material A obtained in step S1 was placed in a hydrogen / argon mixed atmosphere (wherein the hydrogen volume percentage was 10%) at a flow rate of 100 mL / min, and hydrogen and argon were first introduced for 30 min before heating. The temperature was then increased to 500° C. at a heating rate of 5° C. / min and held at that temperature for 2 h to obtain material B;

[0026] Step S3: Grind the material B obtained in step S2 evenly in a mortar for 30 minutes to finally obtain catalyst C.

[0027] Comparative Example 1

[0028] Step S1: 0.2 g of glucose, 0.15 g of dicyandiamide, 0.0305 g of copper chloride and 0.12 g of stannous chloride dihydrate were weighed and ground in a grinding mortar for 15 min to obtain material A1;

[0029] Step S2: Material A1 obtained in step S1 was placed in a hydrogen / argon mixed atmosphere (wherein the hydrogen volume percentage was 10%) at a flow rate of 100 mL / min, and hydrogen and argon were first introduced for 30 min before heating. The temperature was then increased to 500° C. at a heating rate of 5° C. / min and held at that temperature for 2 h to obtain material B1;

[0030] Step S3: Grind the material B1 obtained in step S2 evenly in a mortar for 30 minutes to finally obtain catalyst C1.

[0031] Comparative Example 2

[0032] Step S1: 0.2 g of glucose, 0.08 g of dicyandiamide, 0.0305 g of copper chloride and 0.21 g of stannous chloride dihydrate were weighed and ground in a grinding mortar for 15 min to obtain material A2;

[0033] Step S2: Material A2 obtained in step S1 was placed in a hydrogen / argon mixed atmosphere (wherein the hydrogen volume percentage was 10%) at a flow rate of 100 mL / min, and hydrogen and argon were first introduced for 30 min before heating. The temperature was then increased to 420°C at a heating rate of 5°C / min and held at that temperature for 2 h to obtain material B2;

[0034] Step S3: Grind the material B2 obtained in step S2 evenly in a mortar for 30 min to obtain catalyst C2.

[0035] Comparative Example 3

[0036] Step S1: 0.2 g of glucose, 0.08 g of dicyandiamide, 0.0305 g of copper chloride and 0.15 g of stannous chloride dihydrate were weighed and ground in a grinding mortar for 15 min to obtain material A3;

[0037] Step S2: Material A3 obtained in step S1 was placed in a hydrogen / argon mixed atmosphere (wherein the hydrogen volume percentage was 10%) at a flow rate of 100 mL / min, and hydrogen and argon were first introduced for 30 min before heating. The temperature was then increased to 420°C at a heating rate of 5°C / min and held at that temperature for 2 h to obtain material B3;

[0038] Step S3: Grind the material B3 obtained in step S2 evenly in a mortar for 30 min to obtain catalyst C3.

[0039] Comparative Example 4

[0040] Step S1: 0.2 g of glucose, 0.08 g of dicyandiamide, 0.0305 g of copper chloride and 0.12 g of stannous chloride dihydrate were weighed and ground in a grinding mortar for 15 min to obtain material A4;

[0041] Step S2: Material A4 obtained in step S1 was placed in a hydrogen / argon mixed atmosphere (wherein the hydrogen volume percentage was 10%) at a flow rate of 100 mL / min, and hydrogen and argon were first introduced for 30 min before heating. The temperature was then increased to 420°C at a heating rate of 5°C / min and held at that temperature for 2 h to obtain material B4;

[0042] Step S3: Grind the material B4 obtained in step S2 evenly in a mortar for 30 min to obtain catalyst C4.

[0043] Comparative Example 5

[0044] Step S1: 0.2 g of glucose, 0.15 g of dicyandiamide, 0.0305 g of copper chloride and 0.12 g of stannous chloride dihydrate were weighed and ground in a grinding mortar for 15 min to obtain material A5;

[0045] Step S2: Material A5 obtained in step S1 was placed in a hydrogen / argon mixed atmosphere (wherein the hydrogen volume percentage was 10%) at a flow rate of 100 mL / min, and hydrogen and argon were first introduced for 30 min before heating. The temperature was then increased to 420°C at a heating rate of 5°C / min and held at that temperature for 2 h to obtain material B5;

[0046] Step S3: Grind the material B5 obtained in step S2 evenly in a mortar for 30 min to obtain catalyst C5.

[0047] Comparative Example 6

[0048] Step S1: 0.2 g of glucose, 0.08 g of dicyandiamide, and 0.12 g of stannous chloride dihydrate were weighed and ground in a grinding mortar for 15 min to obtain material A6;

[0049] Step S2: Material A6 obtained in step S1 was placed in a hydrogen / argon mixed atmosphere (wherein the hydrogen volume percentage was 10%) at a flow rate of 100 mL / min, and hydrogen and argon were first introduced for 30 min before heating. The temperature was then increased to 420°C at a heating rate of 5°C / min and held at that temperature for 2 h to obtain material B6;

[0050] Step S3: Grind the material B6 obtained in step S2 evenly in a mortar for 30 min to obtain catalyst C6.

[0051] Comparative Example 7

[0052] Step S1: 0.2 g of glucose, 0.08 g of dicyandiamide, and 0.12 g of stannous chloride dihydrate were weighed and ground in a grinding mortar for 15 min to obtain material A7;

[0053] Step S2: Material A7 obtained in step S1 was placed in a hydrogen / argon mixed atmosphere (wherein the hydrogen volume percentage was 10%) at a flow rate of 100 mL / min, and hydrogen and argon were first introduced for 30 min before heating. The temperature was then increased to 420°C at a heating rate of 5°C / min and held at that temperature for 2 h to obtain material B7;

[0054] Step S3: Grind the material B7 obtained in step S2 evenly in a mortar for 30 min to obtain catalyst C7.

[0055] The catalyst C and catalysts C1 to C7 of the present invention are used to catalyze the co-reduction of carbon dioxide and nitrate to synthesize urea. The specific process is as follows: 2 mg of the prepared catalyst is dispersed in a mixed solution of water, ethanol and Nafion, and after ultrasonic dispersion, the solution is dripped onto carbon paper and dried under a heat lamp. H-type electrodes are used for testing, with Ag / AgCl electrodes and platinum sheets serving as reference electrodes and counter electrodes, respectively. The electrolyte is a 0.1M KNO3+0.1MKHCO3 solution saturated with carbon dioxide. Urea is detected by the diacetyl monoxime method, and the results are as follows. Figure 4 shown.

[0056] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a Cu3Sn alloy electrocatalyst, characterized in that The specific preparation steps are: Step S1, grinding and mixing glucose, dicyandiamide, copper chloride and stannous chloride dihydrate to obtain material A, wherein the mass ratio of glucose, dicyandiamide, copper chloride and stannous chloride dihydrate is 0.2:0.08:0.0305:012; Step S2, transferring the material A obtained in step S1 into a tube furnace, sintering it at 420-500° C. for 2 h in a hydrogen / argon mixed atmosphere, and then naturally cooling it to room temperature to obtain material B; Step S3, grinding the material B obtained in step S2 uniformly to obtain a Cu3Sn alloy electrocatalyst.

2. The method for preparing the Cu3Sn alloy electrocatalyst according to claim 1, wherein: In step S1, the glucose, dicyandiamide, copper chloride and stannous chloride dihydrate are ground under a heating lamp for 10 to 20 minutes; in step S3, the grinding time is 30 to 50 minutes.

3. The method for preparing the Cu3Sn alloy electrocatalyst according to claim 1, wherein: The volume percentage of hydrogen in the hydrogen / argon mixed atmosphere in step S2 is 10%, and the flow rate of the hydrogen / argon mixed atmosphere is 50-100 mL / min.

4. The method for preparing the Cu3Sn alloy electrocatalyst according to claim 1, characterized in that The specific preparation steps are: Step S1, grinding 0.2 g of glucose, 0.08 g of dicyandiamide, 0.0305 g of copper chloride and 0.12 g of stannous chloride dihydrate in a grinding mortar for 15 min to obtain material A; Step S2: Material A obtained in step S1 was placed in a hydrogen / argon mixed atmosphere at a flow rate of 100 mL / min, and hydrogen and argon were first passed through for 30 minutes before heating, and then heated to 500°C at a heating rate of 5°C / min and kept at this temperature for 2 hours to obtain material B; Step S3: Grind the material B obtained in step S2 in a mortar to obtain a Cu3Sn alloy electrocatalyst.

5. Use of the Cu3Sn alloy electrocatalyst prepared according to the method according to any one of claims 1 to 4 in the synthesis of urea by reducing carbon dioxide and nitrate.

6. The use according to claim 5, characterized in that The specific process is as follows: 2 mg of the prepared electrocatalyst is dispersed in a mixed solution of water, ethanol and Nafion. After ultrasonic dispersion, the solution is dripped onto carbon paper and dried under a heat lamp. The test is carried out using an H-type electrode, with an Ag / AgCl electrode and a platinum sheet as the reference electrode and counter electrode, respectively. The electrolyte is a 0.1M KNO3+0.1M KHCO3 solution saturated with carbon dioxide. The yield of urea synthesis catalyzed by the Cu3Sn alloy electrocatalyst reaches 539.8µgh. -1 mg -1 , the Faraday efficiency reaches 50.5%.

Citation Information

Cited By

  • Electrode for electrocatalytic synthesis of urea as well as preparation method and application of electrode

    CN122105506A